Pengembangan Modul Struktur Atom Berbasis Guided Discovery Learning untuk Kelas X SMA - Yondriadi Yondriadi; Yerimadesi Yerimadesi (Edukimia, 2019)
This research is aimed at developing a atomic structure module based on guided discovery learning for grade X SMA and determining the level of validity and practicality. The type of research used is Research and Development. The development model used is Plomp model which consists of 3 stages, namely: 1) preliminary research, 2) prototyping stage, and 3) assessment phase. The validity test of this module was done by two chemistry lecturers at FMIPA UNP, two chemistry teachers  at SMAN 3 Pariaman, and a chemistry teachers at SMAN 4 Pariaman using validation instrument. Practicality test was done by 2 chemistry teachers at SMAN 3 Pariaman and 34 students X MIPA 1 of SMAN 3 Pariaman using practicality questionnaires. Validity instrument and practicality questionnaires were analysed by Cohen Kappa (k) Formula. The results of the analysis of the validity with an average score of the kappa moment 0.86 which is very high category of validity. The results of teachers practice analysis, and the practicality of students show the average score of the moment of kappa (k) in a row is 0.90 which is a very high practicality category and 0.84 which is also a very high practicality category. The data obtained shows that the atomic structure module based on guided discovery learning for grade X SMA produced is valid and practical.